Análisis de los ingresos recaudados por sunat en el régimen especial de renta por actividad económica manufactura, periodo 2017 – 2019 - Vergara Pizango, Joicy Jajaira (2022)
Tax collection represents a fundamental and important activity developed by the tax administration - SUNAT, which consists of generating the largest collection of income from tax concepts, which will allow financing public spending. The present investigation called "Analysis of the income collected by SUNAT in the Special Income Regime by Economic Activity Manufacturing, period 2017 - 2019", had the general objective of determining the evolution of the income collected by SUNAT in the special income regime by Manufacturing economic activity during the period 2017 to 2019. Likewise, the research was of a quantitative type and of a descriptive, non-experimental - transversal design. From the analysis and discussion of the results obtained, it was possible to determine that the income collected by SUNAT presents a positive evolution for the study period.